2021
DOI: 10.1136/neurintsurg-2021-017349
|View full text |Cite
|
Sign up to set email alerts
|

Stroke thrombectomy complication management

Abstract: Endovascular mechanical thrombectomy (EVT) is widely accepted as the first-line treatment for acute ischemic stroke in patients with large vessel occlusion. Being an invasive treatment, this method is associated with various preoperative, perioperative, and postoperative complications. These complications may influence peri-interventional morbidity and mortality and therefore treatment efficacy and clinical outcome. The aim of this review is to discuss the most common types of complications associated with EVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 56 publications
0
39
0
1
Order By: Relevance
“…Procedure-related SAH after mechanical thrombectomy has been reported as a benign clinical feature that does not require additional surgical procedures [ 1 , 3 , 5 , 7 ]. In one case, SAH after mechanical thrombectomy was suggested to be related to injury of the arterial wall during stent retrieval, but no definite offending lesion was usually observed [ 7 ], this was attributed to the spontaneous cessation of the SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Procedure-related SAH after mechanical thrombectomy has been reported as a benign clinical feature that does not require additional surgical procedures [ 1 , 3 , 5 , 7 ]. In one case, SAH after mechanical thrombectomy was suggested to be related to injury of the arterial wall during stent retrieval, but no definite offending lesion was usually observed [ 7 ], this was attributed to the spontaneous cessation of the SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Pilgram-Pastor et al 2021 suggest a rate of 0.5 -1 mg nimodipine i.a. over several minutes and points out the risk of hypotension and steal phenomena [3]. Others suggest the use of 2 -5 mg nicardipine i.a.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al described arterial vasospasms after stent-retriever thrombectomy in 2009 [1]. Since 2015, with the establishment of endovascular stroke treatment (EST) as a first-line therapy for acute ischemic stroke, more research emerges concerning the management of procedure failure and interventional complications [2,3]. In the early randomized multicenter studies of 2015, only REVASCAT and SWIFT PRIME reported on vasospasms with fourteen cases of vasospasms in the intervention group of REVASCAT (14/103, 13.6 %), four of which required treatment by application of vasodilating medication, and four reported cases of vasospasm (4/98, 4 %) in the intervention group of SWIFT PRIME [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, no RCTs exist that include local anesthesia as a comparator arm and meta-analyses of observational studies have failed to show differences in functional outcomes with LA compared to CS and GA. Some of these studies show evidence of shorter door-to-needle time in patients and less intraprocedural hypotension, which are important considerations for functional outcomes [41].…”
Section: Anesthetic Strategiesmentioning
confidence: 99%